PENERAPAN SNAKES AND LADDERS GAME UNTUK MENINGKATKAN KEMAMPUAN SPEAKING MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR - Aisah; Elfi Lailan Syamita Lubis; Sakura Alwina; Anisa Noverita; Muhammad Irzaldi (LPPM STKIP AL MAKSUM, 2024)
This research is based on the difficulties of students in learning for elementary school (English for Children) courses. In essence, this class action research aims to improve speaking skills in speaking for elementary school courses by using the snakes and ladders game approach. This research was carried out at the Al Maksum College of elementary school teacher education study program in brade III-C. The instruments used consisted of the test instruments, namely speaking ability test questions and non-tests in the form of the students activity observation sheets. The results of this study show that speaking ability from cycle I to cycle II has increased with an average score of 68.5 in cycle I to 82.0 in cycle II as well as the entire learning process carried out from cycle I to cycle II has also increased. Therefore, it can be concluded that the snakes and ladders game approach can improve students’ speaking skills in the Speaking for Elementary School Course.